Exploring the Power of Sulfur, Silicon, and Organocatalysis: Innovative Strategies for Asymmetric Synthesis and Advanced Synthetic Methodology - Chiu, Kuei-Wei; Chein, Rong-Jie (Synlett, 2023)
This research Account describes the development of chiral organocatalysts, focusing on diphenyl-2-pyrrolidinemethanol and its derivatives as valuable tools in asymmetric transformations. The research also includes the discovery of a novel anionic Si→C alkyl migration method, which has been developed into a one-pot procedure for synthesizing (E)-chalcones from hydroxyamide and N,N-diethylcarbamates. The findings underscore the potential of sulfide and silicon as valuable reagents for organic synthesis and emphasize the importance of exploring new reaction pathways and mechanisms to discover novel synthetic methods.1 Introduction2 Synthesis of 2 and Sulfur Reagent as Chiral Lewis Acid3 Sulfur/Selenium Reagent as Chiral Lewis Base4 Anionic Si→C Alkyl Migration5 Conclusion
Keywords: asymmetric catalysis; organocatalysis; oxathiaborolium; chiral sulfide; chiral selenide; alkyl migration; anionic Snieckus–Fries rearrangement